Depth resolved grazing incidence neutron scattering experiments from semi-infinite interfaces: a statistical analysis of the scattering contributions. (26th March 2018) - Adlmann, Franz A; Herbel, Jörg; Korolkovas, Airidas; Bliersbach, Andreas; Toperverg, Boris; Van Herck, Walter; Pálsson, Gunnar K; Kitchen, Brian; Wolff, Max
Abstract: Grazing incidence neutron scattering experiments offer surface sensitivity by reflecting from an interface at momentum transfers close to total external reflection. Under these conditions the penetration depth is strongly non-linear and may change by many orders of magnitude. This fact imposes severe challenges for depth resolved experiments, since the brilliance of neutron beams is relatively low in comparison to e.g. synchrotron radiation. In this article we use probability density functions to calculate the contribution of scattering at different distances from an interface to the intensities registered on the detector. Our method has the particular advantage that the depth sensitivity is directly extracted from the scattering pattern itself. Hence for perfectly known samples exact resolution functions can be calculated and visa versa. We show that any tails in the resolution function, e.g. Gaussian shaped, hinders depth resolved experiments. More importantly we provide means for a descriptive statistical analysis of detector images with respect to the scattering contributions and show that even for perfect resolution near surface scattering is hardly accessible.